Frequent blood donation and offspring birth weight—a next‐generation association?. Issue 3 (5th December 2018) - Rigas, Andreas S.; Pedersen, Ole B.; Sørensen, Erik; Thørner, Lise W.; Larsen, Margit H.; Katz, Louis M.; Nielsen, Kaspar; Titlestad, Kjell; Edgren, Gustaf; Rostgaard, Klaus; Erikstrup, Christian; Hjalgrim, Henrik; et al.
Abstract : BACKGROUND: The prevalence of iron depletion is high among premenopausal women who donate blood frequently. Studies in nondonor populations indicate that iron deficiency anemia is associated with an increased risk of low birth weight. This prompts concerns that iron deficiency induced by frequent blood donation might impair subsequent fetal development. STUDY DESIGN AND METHODS: The aim of this study was to assess whether prepregnancy donation intensity affects the birth weight of singletons born at term (gestational week 38 or later) to nulliparous female donors in Denmark. We identified 293, 897 first live singleton births to Danish women between 1997 and 2012 with complete information on gestational age, birth weight, child sex, parental age, maternal smoking status during pregnancy, and parental education length and annual income. Linear regression analysis was applied, with birth weight as outcome, number of donations within the 3 years before pregnancy as the explanatory variable, and confounding variables as described. RESULTS: Birth weight among children of low‐intensity donors (n = 22, 120) was 12.6 g (95% confidence interval, 6.7–18.6) higher than nondonors (n = 268, 253) after controlling for the above‐mentioned factors. The higher birth weight among low‐intensity donors can be explained by the healthy donor effect. In fully adjusted analyses, birth weight among children of high‐intensity donors (n = 3, 524) was 20.2 g (95% confidence interval, 5.1–35.3 g) lower compared with low‐intensity donors. This reduced birth weight among high‐intensity donors compared to low‐intensity donors may reflect blood donation–induced iron deficiency. CONCLUSIONS: Our results show that high prepregnancy donation intensity is inversely associated with birth weight of singletons born at term to nulliparous women.